Experience of midwives in providing care to labouring women in varied healthcare settings: A qualitative study - Marie Hastings-Tolsma; Annie Temane; Oslinah B. Tagutanazvo; Sanele Lukhele; Anna G. Nolte (AOSIS, 2021)
Background: Midwives are essential to timely, effective, family-centred care. In South Africa, patients have often expressed dissatisfaction with the quality of midwifery care. Negative interpersonal relationships with caregivers, lack of information, neglect and abandonment were consistent complaints. Less is known about how midwives experience providing care. Aim: This research explored and described the experiences of midwives in providing care to labouring women in varied healthcare settings. Setting: Midwives practicing in the Gauteng province, South Africa, in one of three settings: private hospitals, public hospitals or independent maternity hospital. Methods: A convenience sample of midwives (N = 10) were interviewed. An exploratory and descriptive design, with individual semi-structured interviews conducted, asked a primary question: 'How is it for you to be a midwife in South Africa?' Transcribed interviews were analysed using thematic coding. Results: Five themes were found: proud to be a midwife, regulations and independent function, resource availability, work burden and image of the midwife. Conclusion: Midwives struggle within systems that fail to allow independent functioning, disallowing a voice in making decisions and creating change. Regardless of practice setting, midwives expressed frustration with policies that prevented utilisation consistent with scope of practice, as well as an inability to practice the midwifery model of care. Those in public settings expressed concern with restricted resource appropriation. Similarly, there is clear need to upscale midwifery education and to establish care competencies to be met in providing clinical services. Contribution: This research provides evidence of the midwifery experience with implications for needed health policy change.